RNA Technologies and Their Applications - Erdmann, Volker A.; Barciszewski, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
RNA technologies are the driving forces of modern medicine and biotechnology. They combine the fields of biochemistry, chemistry, molecular biology, cell biology, physics, nanotechnology and bioinformatics. The combination of these topics is set to revolutionize the medicine of tomorrow. After more than 15 years of extensive research in the field of RNA technologies, the first therapeutics are ready to reach the first patients. Thus we are witnessing the birth of a very exciting time in the development of molecular medicine, which will be based on the methods of RNA technologies. This volume is the first of a series. It covers various aspects of RNA interference and microRNAs, although antisense RNA applications, hammerhead ribozyme structure and function as well as non-coding RNAs are also discussed. The authors are internationally highly respected experts in the field of RNA technologies
The Key Features of RNA Silencing -- Selected Strategies for the Delivery of siRNA In Vitro and In Vivo -- RNAi Suppression and Its Application -- Strategies to Prevent siRNA-Triggered Cellular Toxicity -- RNAi in Malignant Brain Tumors: Relevance to Molecular and Translational Research -- Silencing Huntington$1 (Bs Disease Gene with RNAi -- Application of Dicer-Substrate siRNA in Pain Research -- RNAi Treatment of HIV-1 Infection -- Application of RNA Interference to Treat Conditions Associated with Dysregulation of Transient Receptor Potential Vanilloid 1 Channel -- Harnessing RNAi-Based Functional Genomics to Unravel the Molecular Complexity Underlying Skin Pigment Variation -- mRNA Structure and its Effects on Posttranscriptional Gene Silencing -- Antisense RNA-Mediated Regulation of the p53 Tumor Suppressor -- Antisense Oligonucleotides: Insights from Preclinical Studies and Clinical Trials -- What can the New Hammerhead Ribozyme Structures Teach us About Design? -- microRNA Biogenesis and its Impact on RNA Interference -- MicroRNAs in Epithelial Antimicrobial Immunity -- Emerging Roles of Long Noncoding RNAs in Gene Expression and Intracellular Organization -- Noncoding RNAs as Therapeutic Targets -- Noncoding RNAs at H19/IGF2 Locus: Role in Imprinting, Gene Expression, and Associated Pathologies.s
Keywords: Medicine; Human genetics; Nucleic acids; Cytology; Biomedicine; Molecular Medicine; Nucleic Acid Chemistry; Human Genetics; Cell Biology